Tingkat Kecemasan Atlet Jujitsu Puslatda Jatim Dalam Menghadapi Pertandingan Pra-PON 2023 - Maulana David; Himawan Wismanadi; Pudjijuniarto Pudjijuniarto; Anindya Mar’atus Sholikhah (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated to determine the level of anxiety of East Java Puslatda athletes in facing the 2023 Pre-PON competition in jujitsu. This study used quantitative descriptive research with research totaling 7 jujitsu athletes from the East Java Puslatda. Data obtained from questionnaires distributed through google forms and data analysis techniques using descriptive analysis techniques using average or mean calculation techniques. The overall results of this study on jujitsu athletes from the East Java Puslatda averaged anxiety in the medium category with a percentage of 71.42%. With a total of 5 athletes belonging to the medium category and 2 athletes belonging to the high category. In statistical calculations, it can be seen from various aspects such as motor aspects, it can be seen that athletes from the East Java Puslatda are in the moderate anxiety category with an average score of 14 from the highest score, which is 22. In the affective aspect, there is a medium category with an average score of 4.5 from the highest score, which is 9. In the somatic aspect, there is a high category with an average score of 15.4 from the highest score of 22. In the cognitive aspect, there is a medium category with an average score of 5.1 from the highest score, which is 10. Thus, it can be concluded that East Java Puslatda jujitsu athletes in the fighter and newaza categories have moderate levels of anxiety.